MEKTEPKE ShEKEMGI JASTAǴÍ BALALARDA LOGIKALÍQ PIKIRLEWDI RAWAJLANDÍRÍW BOYÍNShA ALDÍNǴÍ TÁJIRIYBELER (ShET EL MÁMLEKTLERI MÍSALÍNDA) - Isnaddinova, A. (SCIENCE and SOCIETY, 2025)
This article analyzes advanced practices used in the preschool education systems of countries such as Finland, Japan, Italy, Singapore, and the United Kingdom. These countries employ various approaches such as play-based learning, research-based projects, logic games, and early childhood mathematics systems to foster logical thinking skills in children. The research results show that a balance between child-centered education and teacher guidance is essential for effectively developing logical thinking.